Project-based learning via school-university collaboration: impact on general pedagogical knowledge in primary student-teachers - Yessimbekova, Assylzhan; Taurbekova, Ainur; Shagatayeva, Zaure; Zhanatbekova, Nazym; Shakarim, Nurdaulet (Frontiers in Education, 2025)
BackgroundService-learning, though prevalent in Western academia, remains nascent in Eurasian educational contexts. This study probes the pedagogical efficacy of a school-university partnership initiative, engaging primary education student-teachers as teaching assistants in elementary settings. Existing scholarship highlights service-learning’s capacity to bridge theoretical and practical realms, bolster professional skills, and elevate self-efficacy. Yet, empirical insights into its impact on general pedagogical knowledge (GPK) and teaching self-efficacy, particularly in primary teacher education, are sparse, prompting this investigation.MethodsA quasi-experimental, embedded mixed-methods design was employed, integrating qualitative reflections with quantitative data. Seventy-four undergraduate student-teachers from a primary education program were randomly assigned to a non-engaged (n = 37) or treatment group (n = 37). The latter participated in a service-learning intervention, collaborating with seven public schools to address specific educational challenges. Over 6–12 weeks, pre-service teachers designed and delivered supplemental instructional modules, guided by mentors. GPK and self-efficacy were assessed pre- and post-intervention using validated instruments, complemented by reflective reports.ResultsQuantitative analysis revealed significant GPK gains in adaptivity, structure, and assessment for the experimental group, with notable effect sizes. Teaching self-efficacy showed mixed outcomes. Reflective reports underscored the intervention’s role in linking theory to practice, fostering practical skills, and deepening professional purpose. Challenges included logistical demands and resource constraints.ConclusionProject-based service-learning boosted GPK, bridging theory and practice, though its impact on self-efficacy varies. This study offers a nuanced evaluation, advancing understanding of service-learning’s role in primary teacher education.